2019
DOI: 10.3390/microorganisms8010043
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Engineering of an Iron-Resistant Saccharomyces cerevisiae Mutant and Its Physiological and Molecular Characterization

Abstract: Iron plays an essential role in all organisms and is involved in the structure of many biomolecules. It also regulates the Fenton reaction where highly reactive hydroxyl radicals occur. Iron is also important for microbial biodiversity, health and nutrition. Excessive iron levels can cause oxidative damage in cells. Saccharomyces cerevisiae evolved mechanisms to regulate its iron levels. To study the iron stress resistance in S. cerevisiae, evolutionary engineering was employed. The evolved iron stress-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…The comparative transcriptomic and whole‐genome resequencing results of the silver‐resistant strain 2E revealed that several genes associated with cell wall biogenesis and integrity were either differentially expressed or mutated in 2E, compared with the reference strain (Tables 1 and 2). To test if there were any differences in cell wall integrity between 2E and the reference strain, we performed the lyticase sensitivity assay (Balaban et al, 2020; Kuranda et al, 2006) to both strains, in the presence and absence of silver (200‐μM AgNO 3 ) stress, using the cell wall β‐1,3‐glucan‐degrading enzyme lyticase. Our results revealed that the evolved strain 2E was significantly more resistant to lyticase than the reference strain (Figure 9), implying that the silver‐resistant evolved strain had a higher cell wall integrity or robustness than the reference strain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparative transcriptomic and whole‐genome resequencing results of the silver‐resistant strain 2E revealed that several genes associated with cell wall biogenesis and integrity were either differentially expressed or mutated in 2E, compared with the reference strain (Tables 1 and 2). To test if there were any differences in cell wall integrity between 2E and the reference strain, we performed the lyticase sensitivity assay (Balaban et al, 2020; Kuranda et al, 2006) to both strains, in the presence and absence of silver (200‐μM AgNO 3 ) stress, using the cell wall β‐1,3‐glucan‐degrading enzyme lyticase. Our results revealed that the evolved strain 2E was significantly more resistant to lyticase than the reference strain (Figure 9), implying that the silver‐resistant evolved strain had a higher cell wall integrity or robustness than the reference strain.…”
Section: Resultsmentioning
confidence: 99%
“…Lyticase sensitivity assay was adapted from Kuranda, Leberre, Sokol, Palamarczyk, and François (2006) and performed exactly as described previously (Balaban et al, 2020), using the reference and evolved strain cultures grown under both control and 200-μM AgNO 3 stress conditions; 40-mM 2-mercaptoethanol (Merck, Hohenbrunn, Germany) and 2-U/mL lyticase (Sigma-Aldrich, St. Louis, MO, USA) were used during the experimental procedure. Cell lysis was monitored by absorbance (OD 600 ) measurements every 20 min.…”
Section: Lyticase Sensitivity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The fungal strains useful in iron resistance are Aspergillus niger and Aspergillus foetidus and some Penicillium species too. Fungal strains have good ability for bio leaching process by interfering functional groups of enzymes [105] (Table 12).…”
Section: Iron-resistant Fungimentioning
confidence: 99%
“…Evolutionary selection principles have been used for the improvement of biotechnologically important characteristics, including novel catabolic activities, improved enzyme properties, plasmid functions, and stress resistance ( Sauer, 2001 ; Çakar et al, 2005 , 2012 ). S. cerevisiae strains that are resistant against diverse stress types have been successfully obtained by evolutionary engineering, including nickel-resistant ( Küçükgöze et al, 2013 ), cobalt-resistant ( Çakar et al, 2009 ; Alkim et al, 2013 ), iron-resistant ( Balaban et al, 2020 ), coniferyl aldehyde-resistant ( Hacısalihoğlu et al, 2019 ), caffeine-resistant ( Surmeli et al, 2019 ), ethanol-tolerant ( Turanlı-Yıldız et al, 2017 ), chronologically long-lived ( Arslan et al, 2018a , b ), and silver-resistant ( Terzioğlu et al, 2020 ) S. cerevisiae .…”
Section: Introductionmentioning
confidence: 99%